Creating an Interactive E-book with Augmented Reality for Android Devices - Siahaan, Sabda Dian Nurani; Ruslan, Dede; Fikri, Miftah El; Saragih, Lenti Susanna; Rahmadsyah, Agus (PT FORMOSA CENDEKIA GLOBAL, 2024)
Today's students, both school and school children, tend to seek information from smartphones rather than printed books or newspapers, take notes on their lessons on their smartphones and rarely use notebooks, and even do assignments using smartphones rather than computers or laptops. The problem faced by this study program is the limited teaching materials available, especially for the Green Business course. Currently, students need more visual teaching in order to understand the material well. This study aims to develop an Android-based electronic flipbook with augmented reality technology that is valid, practical, and able to improve student learning outcomes effectively. The research method used was a practicality test, and the results indicated that the developed e-book falls into the highly practical category.